Frictional pull-out work capacity of macro-SSF in concrete composites and evaluation of matrix deterioration due to kinematic fiber-end-slip after full-debonding point - Khabaz, Amjad (Taylor & Francıs Ltd., 2024)
This paper presents a parametric study on the effect of frictional pull-out work capacity on the performance of fiber/matrix regime during the kinematic pull-out process. This study involves an experimental program of pull-out test of straight steel fiber embedded in concrete composites, numerical study based on finite element modeling, and theoretical approaches based on mathematical model. Various parameters were considered such as fiber geometry, Poisson's ratio, elasticity modulus, and aspect ratio. The experimental results were calibrated with the results of numerical study, and the theoretical approaches were controlled using deterioration coefficient based on a given curve of uniaxial stress-displacement relationship plotted experimentally. The results showed that the capacity of pull-out work decreases 62.6% when the fiber diameter decreases 6 times. Decreasing the fiber diameter also improves the resistance of the matrix against deterioration. While decreasing the fiber embedded length by 1.8 times, the frictional pull-out work decreases by 56.3% and boosts relatively the resistance of matrix against crumbling, where the frictional shear bond strength improved by 91%. Likewise, decreasing the fiber aspect ratio by 1.8 times decreases the done frictional pull-out work by 56.3% and boosts the fiber duct resistance against damage by improving the frictional shear bond strength.
Keywords: Deterioration; pull-out work; fiber-end-slip; SSF; frictional shear bond strength